Introduction Of MSME (Micro, Small and Medium Enterprises) Products to Increase Selling Competitiveness at The Level 3 Seuhaaah Festival Event At Paris Van Java Mall - Fajri, Ilham; Karnita, Ita; Wahyono, Surya Aditya; Superwiratni, Superwiratni; Intan, Amalia Juliana Monika; Devi, Ghini Kuntala (Universitas INABA, 2023)
MSMEs (micro, small and medium enterprises) are the main drivers of the Indonesian economy which are now excellent in increasing employment The government in various sectors also helps the development of MSMEs, one of which is by providing KUR (People's Business Credit) loan facilities intended for MSMEs. Now MSMEs are very easy to recognize with various technological advances, one of which is social media which provides one way of promotion attractively. Wikaorganizer invites MSMEs to participate in celebrating the Level 3 Sehaaah Festival which will be held in Paris Van Java in collaboration with BJB held a flash sale in order to celebrate the right one on August 17 and gave vouchers for Rp.17,-. The Community Service program aims to provide education and invite MSMEs to introduce their products to increase their selling competitiveness during the Level 3 Seuhaaah Festival at Paris Van Java Mall. MSME owners were given the opportunity to participate in the event and try to compete with other business units in selling their products. During the Seuhaaah Level 3 Festival, MSMEs could attract consumer attention through creative and attractive product exhibitions. In this case, effective promotion and strong branding are key factors. In addition, participating in events like this allows MSMEs to build a wider business network, including with potential buyers and business partners. In this program, MSMEs can experience real benefits in increasing their sales competitiveness through participation in the Level 3 Seuhaaah Festival event. Therefore, increasing support and promotion of similar events can be an effective strategy in supporting the growth of MSMEs and the local economy as a whole.